AN EMPIRICAL TEST OF ROBERT BLAUNER'S IDEAS ON ALIENATION IN WORK AS APPLIED TO DIFFERENT TYPE JOBS IN A WHITE-COLLAR SETTING. - Kirsch, Barbara A.; Lengermann, Joseph J. (Sociology & Social Research, 1972)
Robert Blauner's ideas on alienating job conditions and feelings of self-estrangement are applied in a study of three types of workers in a white-collar setting. Results indicate that there are substantial differences in the extent to which machine operators, clerical personnel, and computer programmers are subject to the alienating conditions and that there are substantial and corresponding differences in the degree of self-estrangement experienced by these workers. Level of self-estrangement is strongly and positively related to: a) lack of control over the immediate work processes (powerlessness); b) performance of narrow work roles due to an advanced task specialization (meaninglessness); and e) lack of opportunities for promotion.